Tempo e Arqueologia: experiências materiais e imateriais de Antártica - Sarah de Barros Viana Hissa Threlfall (2012)
Antarctica differs from other locations, from its unique geography to the history of its discovery and exploration/exploitation, and the way we insert it in our understanding of the world. It is filled with poetry and mystery, yet, understood as essentially natural and not-human. However, there were seasonal incursions of sealers and whalers in the 19th century, as well as present day seamen, who incorporate Antarctica in their personal experiences. Among those, both groups experience of the perception of time passing is particular is the focus of this study. Specific characteristics of human relations with Antarctica always a temporarypresence and intrinsic aspects of temporal perception consciousness are associated to understand Antarctic time.